Local Wisdom as the Basis of Visual Identity in Handwritten Batik from Sendang Pengilon Salatiga - Utami, Birmanti Setia; Maharani, Penina Inten (Gondang: Jurnal Seni dan Budaya, 2024)
Handwritten Batik from Sendang Pengilon is an enterprise managed by women in Pengilon Village, Salatiga. During the COVID-19 pandemic, this batik enterprise experienced setbacks in terms of sales, leading to a halt in production. After the COVID-19 pandemic ends, the batik business will resume operations with a new visual branding. The objective of this research is to identify various local assets of Pengilon Village that can be processed into the foundation for creating a visual identity. Utilizing local wisdom as the basis for creating a visual identity can provide uniqueness and differentiate Handwritten Batik from Sendang Pengilon among its competitors. A qualitative approach with data analysis using SWOT was employed in this research. The natural resources that constitute the richness of Salatiga, such as the Rejasa flower as a flora of Salatiga and the legendary story of Sendang Pengilon as one of Salatiga's local wisdom, serve as the basis for designing the identity of Batik Sendang Pengilon. This research resulted in a visual identity including a logo, typography, color variations, supergraphics, guidelines for consistent use of visual identity, and examples of visual identity application in various media. The outcomes of this research have been accepted and utilized by Batik Sendang Pengilon. Further development of the visual identity research for Batik Sendang Pengilon can be implemented across various media such as packaging and promotional materials. It is hoped that research on the visual identity of Batik Sendang Pengilon will continue to evolve and provide greater benefits for the specific development of the Batik Sendang Pengilon business and the economic empowerment of the Salatiga community in general.